If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(y + -1) = 9 + -2(-7y + -3) Reorder the terms: 3(-1 + y) = 9 + -2(-7y + -3) (-1 * 3 + y * 3) = 9 + -2(-7y + -3) (-3 + 3y) = 9 + -2(-7y + -3) Reorder the terms: -3 + 3y = 9 + -2(-3 + -7y) -3 + 3y = 9 + (-3 * -2 + -7y * -2) -3 + 3y = 9 + (6 + 14y) Combine like terms: 9 + 6 = 15 -3 + 3y = 15 + 14y Solving -3 + 3y = 15 + 14y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-14y' to each side of the equation. -3 + 3y + -14y = 15 + 14y + -14y Combine like terms: 3y + -14y = -11y -3 + -11y = 15 + 14y + -14y Combine like terms: 14y + -14y = 0 -3 + -11y = 15 + 0 -3 + -11y = 15 Add '3' to each side of the equation. -3 + 3 + -11y = 15 + 3 Combine like terms: -3 + 3 = 0 0 + -11y = 15 + 3 -11y = 15 + 3 Combine like terms: 15 + 3 = 18 -11y = 18 Divide each side by '-11'. y = -1.636363636 Simplifying y = -1.636363636
| 40x^3-35x^2+8x-7= | | 2-5x=3x-5 | | 126=-16x^2+90x | | f(x)=x^2-10x-600 | | x^2-3+x=-21 | | 126=-16x^2+90t | | 430/x=.25 | | (5y-9)(1+y)=0 | | 1-7lnx=0 | | 5r-10=4r | | g(x)=x^2-10x-600 | | 1.2=(x/x-750) | | g(x)=x^2-10x-6000 | | -2(u+5)=4u-6+4(3u+1) | | 2y=y+-1 | | 13x-3(5-3x)= | | x+(2x+1)+(3x+2)=170 | | 1.1X+2.2=9.9 | | 2x+4(x-3)=3x-15 | | 1.2=ln(x/x-750) | | 18x^2+18x=0 | | 0.7X+1.5=3.88 | | 3x(2x^5y^3z^3)/9x^2 | | -2x-1=2x+23 | | (3x-2)(x-4)=6x-4 | | -m-1=2m+5 | | 9/15*4/4= | | 42x^2+36x=0 | | 7/10*180 | | 2t^2-50=0 | | 4t^3-8t^2-140t= | | R^6-64= |